(3fXQjI MGdjI heSJbHdjIs - (3WGQb YHO GdYGd(B, (3MeGOs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2007)
(3GWGQ GYOGO hYQV GdbhGFe GdeGdjI,GdJbGQjQ GdeGdjI (B((3GdeaGgje(B-(3GdCgOGa(B-(3GdNUGFU(B)(3, GdbhGFe GdeGdjI GdCSGSjI (B((3CfhGYgG(B-(3YfGUQgG(B-(3GdYdGbGJ HjfgJ(B)(3, GYOGO hGSJNOGe bGFeI GdeQcR GdeGdj(B((3GdejRGfjI(B)(3, GYOGO hGSJNOGe bGFeI GdONd, GYOGO hGSJNOGe bGFeI GdONd, GYOGO hGSJNOGe bFeI GdJOabGJ GdfbOjI, bGFeI GdJZjQGJ aj Mbhb GdedcjI hGdGjVGMGJ GdeJeeI, bGFeI GdbjeI GdeVGaI, GdJbGQjQ GdbWGYjI habG ddeYGjjQ GdeMGSHjI, GdJbGQjQ GdeGdjI aj Xd GbJUGOjGJ GdJVNe GdLGeM, JbGQjQ eGdjI eSGYOI, JMdjd GdbhGFe GdeGdjI` JWHjbGJ YedjI GdJMdjd GdeGdj(B.s
(3GdeQGLY U(B.529s
Keywords: (3GdJbGQjQ GdeGdjIs; (3GdbhGFe GdeGdjI(B- (3GdEFJeGfs; (3GdbhGFe GdeGdjI(B- (3GdESJKeGQs